2012
DOI: 10.1007/s11420-011-9239-7
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Platelet-Rich Plasma in Inducing Musculoskeletal Tissue Healing

Abstract: Background Platelet-rich plasma [PRP] has received increasing interest across many musculoskeletal disciplines and has been widely applied clinically to stimulate tissue healing in numerous anatomical regions. The known actions of platelet-derived factors suggest that PRP may have significant potential in the treatment of pathological conditions of cartilage, tendon, ligament, and muscle. Purpose The aim of this manuscript is to review current literature regarding the biology of PRP and the efficacy of using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(46 citation statements)
references
References 63 publications
0
44
0
2
Order By: Relevance
“…Although animal models are suitable to observe the systemic effects of PRP, animal tissue physiology and sensitivity differ from those of human tissue. [25][26][27] Concerning the small amount of studies demonstrating the in vitro effects of different leukocyte concentrations of PRP, it was observed that these studies are on synoviocytes. [28] or other tissues such as human ligament fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although animal models are suitable to observe the systemic effects of PRP, animal tissue physiology and sensitivity differ from those of human tissue. [25][26][27] Concerning the small amount of studies demonstrating the in vitro effects of different leukocyte concentrations of PRP, it was observed that these studies are on synoviocytes. [28] or other tissues such as human ligament fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…[28] or other tissues such as human ligament fibroblasts. [26] To the best of our knowledge, in the literature, only one in vitro experimental study tested the effect of PRP on chondrocytes isolated from osteoarthritis tissue. Unfortunately, the cell cultures in this single study were established with tissues isolated only from four male patients.…”
Section: Discussionmentioning
confidence: 99%
“…Heightened catabolism is associated with decreased sheer/tensile strength of soft-tissue and has been correlated with decreased recovery and healing. The potential for PRP to augment the negative effects of neutrophils in the initial stage of healing lends support to the recommendation to avoid its use in the first 24 h following muscle injury and/or to use leukocyte-poor PRP preparations [16]. Because neutrophils may exacerbate original muscle damage some have suggested this provides further rationale to consider leukocytepoor PRP for muscle healing [17,18].…”
Section: Pathophysiology and Mechanisms Of Muscle Healingmentioning
confidence: 98%
“…PRP contains growth factors and three proteins in blood known to act as a matrix for bone, connective tissue, and epithelial migration 8 . The platelets release various growth factors that stimulate angiogenesis, promote vascular growth and fibroblast proliferation, which increase collagen synthesis 9 .…”
Section: Introductionmentioning
confidence: 99%
“…The reasons are due to unanswered questions concerning the dosing, timing, and frequency of PRP injections; distinct techniques for delivery and delivery location (over or within the injured tissue site, or intraarticularly); optimal physiologic conditions for injections; and the combined use of recombinant proteins, cytokines, additional growth factors, biological scaffolds, and stems cells 9,10 . Therefore, there is a need to implement more investigations contemplating both aspects of PRP mechanism of action on different types of muscle lesions as well as new forms of diagnostic tools.…”
Section: Introductionmentioning
confidence: 99%